Rare thromboses of cerebral, splanchnic and upper-extremity veins - Martinelli, Ida; Stefano, Valerio De (Thrombosis and Haemostasis, 2010)
Venous thrombosis typically involves the lower extremity circulation. Rarely, it can occur in the cerebral or splanchnic veins and these are the most frightening manifestations because of their high mortality rate. A third site of rare venous thrombosis is the deep system of the upper extremities that, as for the lower extremity, can be complicated by pulmonary embolism and post-thrombotic syndrome. The authors conducted a narrative review focused on clinical manifestations, risk factors, and treatment of rare venous thromboses. Local risk factors such as infections or cancer are frequent in thrombosis of cerebral or portal veins. Upper extremity deep-vein thrombosis is mostly due to local risk factors (catheter- or effort-related). Common systemic risk factors for rare venous thromboses are inherited thrombophilia and oral contraceptive use; chronic myeloproliferative neoplasms are closely associated with splanchnic vein thrombosis. In the acute phase rare venous thromboses should be treated conventionally with low-molecular-weight heparin. Use of local or systemic fibrinolysis should be considered in the case of clinical deterioration in spite of adequate anticoagulation. Anticoagulation with vitamin K-antagonists is recommended for 3–6 months after a first episode of rare venous thrombosis. Indefinite anticoagulation is recommended for Budd-Chiari syndrome, recurrent thrombosis or unprovoked thrombosis and permanent risk factors. In conclusion, the progresses made in the last couple of decades in diagnostic imaging and the broadened knowledge of thrombophilic abnormalities improved the recognition of rare venous thromboses and the understanding of pathogenic mechanisms. However, the recommendations for treatment mainly derive from observational studies.
Keywords: Cerebral vein thrombosis; Budd-Chiari syndrome; extrahepatic portal vein thrombosis; mesenteric vein thrombosis; upper-extremity deep venous thrombosis